Turbulent Flow In An Active Wind-Driven Ventilation Device - Abolfazl, Sousanabadi Farahani (2009)
Growing concern on environmental issues has prompted house owners and industries to consider use of roof top ventilators, as a passive form of quality air circulation and comfort using only wind energy. However, many of these ventilators have evolved through trial and error and the flow physics associated with these ventilators is barely understood. This study presents prediction of airflow using Computational Fluid Dynamics (CFD) technique code, FLUENT, so as to visualize the flow behavior around and within turbine ventilator in addition to determining the aerodynamic forces acting on a turbine ventilator during operation and comparing the simulated results to available experimental data. The prototype used for this investigation is a wind driven ventilator from Edmonds Company with a rotor diameter of 330 mm and base diameter of 1 50 mm. The free stream velocities in visualization of flow are set to be 7 and 20 m.s-l when, for determining the aerodynamic forces are considered to be 7, 10, 14, 20 and 25 m.s-l corresponding to experiment. The simulated prototype is placed in a control volume with the same dimensions as open circuit wind tunnel used in experimental investigation. Also the operating pressure and fluid properties are set to be the same as experiment. Standard k-E, Realizable k-E, SST k-w and RSM turbulence models are used by taking advantage of moving mesh method to simulate the rotation of turbine ventilator and the consequent results are obtained through the sequential process which ensures accuracy of the computations. The results demonstrated that, the RSM turbulence model shows the best performance on flow visualization and predicting the aerodynamic forces acting on a turbine ventilator. Results from this study, besides ensuring the reliability of utilizing the CFD method in design process of future turbine ventilators, would lead us to a conspicuous progress on increasing the efficiency at reduced cost of wind driven ventilators and similar devices.